2015
DOI: 10.12703/p7-43
|View full text |Cite
|
Sign up to set email alerts
|

The problem of dropout from “gold standard” PTSD therapies

Abstract: Understanding of posttraumatic stress disorder (PTSD) has increased substantially in the past several decades. There is now more awareness of the many different types of trauma that can lead to PTSD, greater refinement of diagnostic criteria, and the development and testing of various treatments for it. As implementation of PTSD therapies has increased, there is also increased attention to the key issues of retention and dropout. Retention refers to the percentage of patients who stay in a treatment for its in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
137
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(142 citation statements)
references
References 44 publications
1
137
1
3
Order By: Relevance
“…Notably, researchers have found that dropout can be higher in community settings ([46,47] although dropout rates do not differ between exposure and non-exposure therapies for PTSD [47]. A meta-analysis pooled across 13 studies found large effect sizes of PE relative to control groups at post-treatment, and medium to large effects at follow up time points [41].…”
Section: Evidence-based Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, researchers have found that dropout can be higher in community settings ([46,47] although dropout rates do not differ between exposure and non-exposure therapies for PTSD [47]. A meta-analysis pooled across 13 studies found large effect sizes of PE relative to control groups at post-treatment, and medium to large effects at follow up time points [41].…”
Section: Evidence-based Treatmentsmentioning
confidence: 99%
“…One of the most important concerns with the sole use of pharmacotherapy for PTSD treatment is the evidence that discontinuing treatment can be associated with relapse [81,83,90]. Although relapse is relatively infrequent after one responds to an evidence-based psychotherapy for PTSD [91], a proportion of patients either drop out of therapy prematurely or do not respond to therapy [46,47,54]. It is therefore critical to continue to investigate new strategies to improve upon the available treatments for PTSD.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Inconsistent findings have been reported for employment status (e.g., Foa et al, 1999; but see Taylor et al, 2003), education (e.g., Rizvi, Vogt, & Resick, 2009; but see Hagenaars, van Minnen, & Hoogduin, 2010), depressive symptoms (e.g., Garcia, Kelley, Rentz, & Lee, 2011; but see Hagenaars, van Minnen, & Hoogduin, 2010), experience of childhood abuse (e.g., van Minnen, Arntz, & Keijsers, 2002; but see Zayfert et al, 2005), and greater PTSD severity (e.g., Marks, Lovell, Noshirvani, Livanou, & Thrasher, 1998; but see Eftekhari et al, 2013). An exception to these mixed findings is that comorbid SUDs have been predictive of dropout from PTSD treatment with some consistency (e.g., Najavits, 2015; Szafranski, Gros, Menefee, Wanner, & Norton, 2014; van Minnen et al, 2002). …”
mentioning
confidence: 99%
“…It bears considering that PA interventions may be more palatable/approachable for older persons than traditional mental health therapies. We report that ten percent of veterans with PTSD in the intervention group withdrew from the study, while drop-out rates for evidence-based psychotherapy for PTSD are reportedly much higher ranging anywhere from 20–80% (Imel, Laska, Jakupcak, & Simpson, 2013; Najavits, 2015). PA programs for veterans with PTSD may also be of interest to clinicians and mental health providers alike, as both a primary and secondary prevention strategy.…”
Section: Discussionmentioning
confidence: 88%